2015
DOI: 10.1161/circgenetics.115.001086
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of the NOTCH1 Receptor as a Cause of Adams–Oliver Syndrome With Variable Cardiac Anomalies

Abstract: A dams-Oliver syndrome (AOS; MIM 100300) is a rare developmental disorder, characterized by a range of abnormalities that include cranial aplasia cutis congenita (ACC) and terminal transverse limb defects.1,2 The spectrum of defects observed implies dysregulation of multiple developmental pathways. Congenital heart defects (CHDs) have been reported in conjunction with AOS in ≤20% of cases and, when present, represent a serious mortality risk.3,4 Cardiac defects are also commonly associated with systemic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
94
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 43 publications
9
94
0
3
Order By: Relevance
“…Recent studies suggest that activation of the NOTCH signaling pathway is related to radiation resistance in tumor cells (19)(20)(21). OncodriveROLE, a machine learning-based approach, indicated that the NOTCH1 p.Cys1374Tyr mutation, as detected in our study, is a "loss-of-function" mutation (22,23). Thus, in our case, loss-of-function in the NOTCH1 gene might have led to radiation sensitivity, resulting in the ability of cells harboring those mutations to be eradicated by radiotherapy.…”
Section: Discussionsupporting
confidence: 63%
“…Recent studies suggest that activation of the NOTCH signaling pathway is related to radiation resistance in tumor cells (19)(20)(21). OncodriveROLE, a machine learning-based approach, indicated that the NOTCH1 p.Cys1374Tyr mutation, as detected in our study, is a "loss-of-function" mutation (22,23). Thus, in our case, loss-of-function in the NOTCH1 gene might have led to radiation sensitivity, resulting in the ability of cells harboring those mutations to be eradicated by radiotherapy.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, mutations in human EOGT have been reported in an autosomal recessive form of a human disease called AdamsOliver syndrome (55,56). Notably, mutations in several Notch pathway components cause an autosomal dominant form of the same disease (39,40,(57)(58)(59). Together, these reports provide strong evidence that O-GlcNAcylation might modulate Notch signaling.…”
Section: Eics Of O-glucose Sites Represented By Peptides Also Containmentioning
confidence: 86%
“…This rare genetic disorder can be autosomal dominant, autosomal recessive or caused by de novo mutations. The autosomal recessive forms are caused by mutations in EOGT, which encodes a component of the Notch pathway, or in DOCK6, which encodes a regulator of Rho GTPase signaling Shaheen et al, 2011Shaheen et al, , 2013Sukalo et al, 2015a,b), whereas the dominant forms are caused by mutations in NOTCH1, RBPJ or DLL4, all of which are Notch pathway components, or in ARHGAP31, which encodes another Rho GTPase regulator (Hassed et al, 2012;Isrie et al, 2014;Meester et al, 2015;Southgate et al, 2011Southgate et al, , 2015Stittrich et al, 2014). In the case of DLL4, it was noted that the disease-associated mutations are distributed throughout the ligand (Meester et al, 2015;Fig.…”
Section: Introductionmentioning
confidence: 99%